Perancangan Aplikasi Komunitas Private Balance Bike Palembang Berbasis Website - syahril, muhammad -; Alviolesa, Bora; Hidayat, Randy (Jurnal Digital: Telnologi Informasi, 2025)
A balance bike is a pedal-less bicycle designed to help children develop balance before transitioning to a regular two-wheeled bicycle. As public interest in this sport continues to grow in Palembang, there is an increasing need for a community platform that can facilitate communication, activity information, and structured member management. This study aims to design a website-based application for the Private Balance Bike Palembang community to support its digital activities. The system development method used is the Waterfall model, which includes requirement analysis, system design, implementation, and testing stages. The result of this research is a website-based application prototype that offers main features such as member registration, discussion forums, training and event schedules, and community data management. This application is expected to be an effective solution for enhancing interaction and coordination among community members in an efficient and organized manner